The donkey of Gallipoli a true story of courage in World War I - Greenwood, Mark 1958- (Candlewick Press, 2008)
Jack and Billy grew up in South Shields, England, where a river carried great ships out to sea. During summer vacation, they led donkeys along the beach for a penny a ride. As they paced the sands of their small town, Jack dreamed that one day he would sail away on a great adventure. Jack's wish came true. During World War I, he served as a stretcher bearer on the battlefields of Gallipoli, Turkey. When stretchers ran short, Jack enlisted the help of a donkey named Duffy, and together these unlikely heroes worked tirelessly, carrying wounded soldiers from the battlefront to the beach hospital. This is a true story of one man and his donkey, and the twist of fate that brought two boyhood friends together one last time.